2018
DOI: 10.32511/juteks.v3i1.201
|View full text |Cite
|
Sign up to set email alerts
|

Kuat Tekan Kolom Beton Ringan Yang Diperkuat Dengan Carbon Fiber Reinforced Polymer Tube

Abstract: Penelitian ini bertujuan untuk menguji sejauhmana FRP tube yang terbuat dari Carbon Fiber Sheet efektif digunakan sebagai material perkuatan kolom beton ringan pada saat kolom tersebut dibebani secara tekan sentris. Sejumlah delapan buah silinder beton ringan dengan ukuran diameter 150 mm dan tinggi 300 mm dicetak dan dites hingga hancur. Kedelapan silinder tersebut terdiri dari dua buah silinder tanpa perkuatan, empat buah silinder dengan perkuatan menggunakan FRP tube, dan dua buah silinder dengan perkuatan … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…(2016)[2] and LoukFanggi et al (2018) [9]. The studies confirmed that the strength and ductility of concrete are significantly improved when FRP is used to strength the concrete Zhou et al (2016) [2].…”
mentioning
confidence: 69%
See 1 more Smart Citation
“…(2016)[2] and LoukFanggi et al (2018) [9]. The studies confirmed that the strength and ductility of concrete are significantly improved when FRP is used to strength the concrete Zhou et al (2016) [2].…”
mentioning
confidence: 69%
“…The studies confirmed that the strength and ductility of concrete are significantly improved when FRP is used to strength the concrete Zhou et al (2016) [2]. conducted the test on lightweight concrete made of ceramsite and steel ring ball as artificial lightweight aggregates (ALWA), and LoukFanggi et al (2018)…”
mentioning
confidence: 75%